Supply Chain Performance Evaluation in the Pulley Manufacturing Industry Using Supply Chain Operations Reference and Analytical Hierarchy Process - Qurtubi; Haswika; Sangkhiew, Noppakun; Kusrini, Elisa (Advance Sustainable Science Engineering and Technology, 2026)
Supply chain performance is critical to the efficiency of make-to-order manufacturing systems, where waste such as waiting, rework, unnecessary motion, overprocessing, and transportation still occurs at several workstations. These inefficiencies prolong production time and reduce overall effectiveness. This study aims to measure supply chain performance, determine the relative importance of performance metrics, and establish improvement priorities. The research integrates the Supply Chain Operations Reference (SCOR) model with the Analytical Hierarchy Process (AHP) to evaluate performance and assign objective weights to key indicators. The analysis focuses on five critical workstations identified as major sources of waste. The results provide an objective performance score, identify key indicators requiring improvement, and offer prioritized recommendations to enhance efficiency. Findings show that indicators such as waiting time and facility layout efficiency still need improvement to reach an excellent performance level. The integration of SCOR and AHP effectively supports decision-making in determining improvement priorities, contributing to a more efficient and productive pulley manufacturing process. This study also offers a structured approach to performance evaluation in make-to-order systems, providing practical insights for decision-makers in Small and Medium Industries (SMIs).